1990
DOI: 10.2307/1591243
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Salmonella enteritidis Infection in Laying Chickens. I. Studies on Egg Transmission, Clinical Signs, Fecal Shedding, and Serologic Responses

Abstract: Laying hens were inoculated orally, intracloacally (IC), or intravenously (IV) with Salmonella enteritidis phage type 8 isolates from a human (E700-87) eggs (Y-8P2), or the ovary of a hen (27A). Oral or IV inoculation of 2 x 10(8) to 4 x 10(8) colony-forming units (CFU) of E700-87 caused depression, anorexia, reduced egg production, diarrhea, and some mortality. Lower doses resulted in milder clinical signs. S. enteritidis was cultured from the shells of a few eggs but not from egg contents. Fecal shedding per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
90
0
7

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(107 citation statements)
references
References 18 publications
10
90
0
7
Order By: Relevance
“…Pathologies such as oophoritis, salpingitis, peritonitis and metritis are frequently encountered at onset and during the laying period, causing losses in egg production (Jordan et al 2005). Most bacteria commonly associated with reproductive tract infections originate from both the ascending and descending route (Gast and Beard 1990;Shivaprasad et al 1990;Hoop and Pospischil 1993;Keller et al 1995). Consequently, before or after eggshell formation, developing eggs can be exposed to bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Pathologies such as oophoritis, salpingitis, peritonitis and metritis are frequently encountered at onset and during the laying period, causing losses in egg production (Jordan et al 2005). Most bacteria commonly associated with reproductive tract infections originate from both the ascending and descending route (Gast and Beard 1990;Shivaprasad et al 1990;Hoop and Pospischil 1993;Keller et al 1995). Consequently, before or after eggshell formation, developing eggs can be exposed to bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Most hens stop shedding the bacteria after approximately three weeks (Shivaprasad et al, 1990;Gast, 2005). However, under stress (water deprivation, viral or coccidial infection, stressful environments and moulting) the hens may resume shedding (Skov et al, 2002).…”
Section: Dynamics Of Salmonella Infection In the Laying Hen Flockmentioning
confidence: 99%
“…Salmonella egg content contamination has been observed most commonly on the yolk membrane (Humphrey et al, 1989a;Timoney et al, 1989;Shivaprasad et al, 1990;Holt, 2000, 2001;Gast et al, 2002;Gast et al, 2013) or in the albumen (Humphrey et al, 1989a;Gast and Beard, 1990;Shivaprasad et al, 1990;Gast and Beard, 1992;Thorns, 2000). Direct contamination inside the yolk is also possible but it is a rare event (Gast and Holt, 2001;Gast et al, 2003).…”
Section: Primary Contaminationmentioning
confidence: 99%
“…They, however, studied a phage type 13a strain. Shivaprasad et al (1990) found different results depending on the strain of phage type 8 used. A human strain produced clinical disease in hens and a few eggs had infected shells.…”
Section: Food-poisoning Salmonellaementioning
confidence: 99%